2017
DOI: 10.1175/jpo-d-15-0249.1
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Fixed-Location Observations of Turbulence Advected by Waves: Insights from Spectral Models

Abstract: Assigning a physical interpretation to turbulent fluctuations beneath waves is complex because eddies are advected by unsteady wave orbital motion. Here, the kinematic effects of wave orbital motion on turbulent fluctuations at a fixed location were investigated using model turbulence spatial spectra (κ spectra) together with a general form of the frozen turbulence approximation. Model autospectra and cospectra included an inertial subrange, a rolloff at energy-containing scales (L = 2π/κ0), and a dissipation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…The key simplification is the assumption that the TKE dissipation rate is a 1D field with a robust average in time. A more realistic approach would evaluate the effect on the velocity field [as was done in Lumley and Terray (1983) and Rosman and Gerbi (2017)], rather than directly on the higher statistical moments of the velocity field (i.e., the TKE dissipation rate). Such a description would require knowledge of how the velocity field statistics vary with depth a priori.…”
Section: A Model Parametersmentioning
confidence: 99%
“…The key simplification is the assumption that the TKE dissipation rate is a 1D field with a robust average in time. A more realistic approach would evaluate the effect on the velocity field [as was done in Lumley and Terray (1983) and Rosman and Gerbi (2017)], rather than directly on the higher statistical moments of the velocity field (i.e., the TKE dissipation rate). Such a description would require knowledge of how the velocity field statistics vary with depth a priori.…”
Section: A Model Parametersmentioning
confidence: 99%
“…Using this method, the turbulence characteristics in the surf zone were studied (Feddersen, , ). Rosman and Gerbi () confirmed that the method for the estimation of the TKE dissipation rate proposed by Feddersen et al () is robust.…”
Section: The Results Of the Observationsmentioning
confidence: 68%
“…In order to check the kinematic effects of wave advection on the estimated RSs using Eq. 26, we use analytical shapes for the turbulence (co)spectra in the framework of the kinematic model proposed by Lumley and Terray (1983) and extended by Rosman and Gerbi (2017).…”
Section: Wave Bias Correctionmentioning
confidence: 99%